Comprehensive nuclear proteome of Arabidopsis obtained by sequential extraction. (1st January 2019) - Goto, Chieko; Hashizume, Shoko; Fukao, Yoichiro; Hara-Nishimura, Ikuko; Tamura, Kentaro
ABSTRACT: In eukaryotes, the nucleus plays key roles in fundamental cellular processes, including DNA replication, chromatin maintenance, transcription, and translation. To better understand the functional diversity of nuclei, we developed a method for the comprehensive extraction of the nuclear proteome from Arabidopsis . We used a buffer with a high sucrose concentration to purify nuclei and then conducted solubility-based fractionation to increase proteome coverage. We identified 1539 proteins and two novel nuclear envelope (NE) proteins in the nuclear fraction of Arabidopsis cultured cells. The localization of 25 proteins was determined by GFP fusion analyses; 23 of these proteins were localized either in the nucleus or the NE-associated endoplasmic reticulum. This result was indicative of the high quality of the proteome. These findings will be useful for clarifying novel nuclear functions in plants.